Potret Manajamen Pendidikan Non-Formal Di Lembaga Kursus - Sukri, Muhammad; Sri Ramdhani, Andi; Azzara Azwan, Anisah; Ansar, Ahlun; Arismunandar, Arismunandar (Universitas Pakuan, 2025)
PORTRAIT OF NON-FORMAL EDUCATION MANAGEMENT IN COURSE INSTITUTIONSNonformal education institutions play a strategic role in improving community competencies to adapt to the evolving world of work. This study aims to analyze the operational quality and social impact of the nonformal course institution CV. Aliah Cipta Sarana in Makassar City. The study employs a descriptive qualitative approach with observation, interviews, and documentation as data collection techniques. The results show that the institution applies a practice-oriented learning model using modules and syllabi aligned with government standards. Teaching staff possess relevant academic qualifications and additional competency certifications. The facilities are adequate, with clean and well-ventilated classrooms and comprehensive learning media such as whiteboards, projectors, computers, and practice equipment for tailoring and driving courses. Funding sources include leadership capital and participant fees, managed transparently. Although institutional partnerships are still limited, cooperation with the Department of Manpower has been established through a computer training program. The institution has a significant impact on enhancing participants’ skills, contributing to social and economic empowerment, and gaining recognition from various stakeholders. This study confirms that nonformal course institutions like CV. Aliah Cipta Sarana play a crucial role in developing human resources and fostering skill-based education in Indonesia.